The activity of azithromycin against Leishmania (Viannia) braziliensisand Leishmania (Leishmania) amazonensis in the golden hamster model - Sinagra, Angel (2007)
Fil: Sinagra, Angel. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.